The Clash of Civilization: A Prognosis of the Future or the Lure of the Past - Taufik Abdullah (Jurnal Masyarakat dan Budaya, 1997)
The story begins when Samuel P. Huntington â€“ the famous political scientist from a highly prestigious university, Harvard University and a citizen of the strongest power on earth â€“ write an articles, entitled â€œThe Clash of Civilization?â€ in Foreign Affairs. Soon enough the article invites highly critical comments from several scholars. Not someone who can easily be set aside, Huntington give his response to his critics by asking a challenging question, â€œIf not civilizations, What?â€ If anything the criticism only harden his conviction that civilization, instead of ideology, economy, or whatever, would become the basis of conflict in the post cold war. He doesnâ€™t stop with this rather cynical question, he writes a book with the same subject and title, but without a question mark. Huntington, â€œthe seekerâ€, has in the meantime become the â€œtrue believerâ€ â€“ as Eric Hoffer would have called him. He also defends his position in several interview he gives after the publication of the book.